Pelatihan Pembuatan Pupuk Organik Menggunakan Limbah Ayam Potong - Lily Joris; Shirley Fredriksz; Jeffrie Wattimena (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
The purpose of this training is to provide understanding, competence and skills for training participants about the utilization of waste from broiler farms (litter) to be used as organic fertilizer, so that it can increase the income of farmers and can reduce negative impacts on the environment. The training method includes lectures, discussion, visits to broiler farm locations and practical work on making organic fertilizer for 30 training participants. Lectures and practical work on making organic fertilizer were carried out at the Animal Production Laboratory of the Animal Husbandry Department, Faculty of Agriculture, Pattimura University. The results of the activity showed an increase in understanding of the management of waste from broiler farms to be managed properly. The conclusion of the Community Service Program Training on Making Organic Fertilizer Using Broiler Manure is as follows: This training succeeded in increasing 92,56 percent the knowledge, competence and skills of participants regarding the processing of broiler waste (litter) into quality organic fertilizer; This training provides an effective solution to overcome the problem of broiler waste (litter) accumulation in the livestock environment; This training changed the perspective of training participants on producing and commercializing organic fertilizer, so that it can increase the income of farmers.